Pendidikan Agama Dalam Perjanjian Baru Tinjauan Periode: Romawi-Yunani, Yudaisme dan Kekristenan - Pasuhuk, Chris; Pardosi, Milton Thorman; Hendriks, Alvyn Cesarianto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education is one of the most important things in every human's life. Because through education, everyone can know many things, have a lot of knowledge and have a lot of experience. However, if education only emphasizes knowledge, then education will only produce people who are smart but have bad morals. Religious Education based on the Bible. The Bible reveals that humans are God's creation who must glorify God, so that education does not only talk about science, but also morality and integrity of life in accordance with the call and demands of God's morality. As developments in Biblical civilization, especially in the Roman-Greek era, Judah, and early Christianity showed the importance of religious life. Religious education as in Matthew 28:19-20 can be understood to have the aim of making disciples, and religious education means to correct errors and lead to truth, and religious education is part of the Great Commission. Because it is the Great Commission, religious education is also very important and must be done as important as preaching the Gospel. Or perhaps more clearly, evangelism and teaching about religion must go together.